Rekayasa Pemekaran dan Tekstur Keripik Buah Nangka Selama Penggorengan Vakum - Jamaluddin .; Budi Rahardjo; Pudji Hastuti; Rochmadi . (Jurnal Keteknikan Pertanian, 2009)
Rising and development also hard and crispy are the specific characteristic of the fry product that acceptableby consumer. To produce rising and texture of the fry product according to the consumer requirement it wasnecessary to control process conditions, take account of characteristic and transformation of raw materialduring frying process. The change of volume (rising and shrinkage) and texture (hardness and crispy) arehappened during frying process of food materials. Volume and texture change were predicted affected byevaporation of water and decreasing of starch content on solidity. This research is done with aim to developmodel of Jackfruit texture and volume change during vacuum frying caused by decreasing of water contentand starch content. As the sample of the research was used the fresh Jackfruit frying on vacuum withtemperature of 70, 80, 90 and 100 OC, with frying duration of 15 to 60 minute and with vacuum pressure of80, 85, 90 kPa. The analyses parameters were consist of volume, texture, water content, and starch contentof the sample before and after frying. Result of the research shows that the higher of the temperature andpressure of the vacuum frying the lower of the starch content and water content of the jackfruit chip. Themathematical model that was developed can be used to predict the change of the jackfruit’s chip textureand volume during vacuum frying.Keywords : jackfruit, vacuum frying, Chip, textureDiterima: 7 Mei 2009; Disetujui: 16 September 2009